PRODUCT PLATFORM SCREENING AT LEGO - Mortensen, Niels Henrik; Jensen, Thomas Steen; Nielsen, Ole Fiil (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Product platforms offer great benefits to companies developing new products in highly competitive markets. Literature describes how a single platform can be designed from a technical point of view, but rarely mentions how the process begins. How do companies identify possible platform candidates, and how do they assess if these candidates have enough potential to be worth implementing? Danish toy manufacturer LEGO has systematically gone through this process twice. The first time the results werepoor; almost all platform candidates failed. The second time, though, has been largely successful after a few changes had been applied to the initial process layout. This case study shows how companies must focus on a limited selection of simultaneous projects in order to keep focus. Primary stakeholders must be involved from the very beginning, and short presentations of the platform concepts should be given to them throughout the whole process to ensure commitment.